PERANCANGAN PROTOTYPE JEMURAN PINTAR BERBASIS ARDUINO UNO R3 MENGGUNAKAN SENSOR LDR DAN SENSOR AIR - Nasrun Marpaung (RJOCS (Riau Journal of Computer Science), 2017)
The use of technology on clothes hangers to create smart clothes hangers which  can read weather conditions so they can go in and out our house or our garage automatically. To be able to read weather conditions, this prototype needs light censor (LDR) which acts as the reader of light condition whether it’s dark or bright, and water censor which acts as a detector of rainy weather. The purposes of this skripsi are: 1) To design a prototype of smart clothes hanger. 2) To plan an innovation for household activities. 3) To design and implement Arduino Uno R3 hardware and software, censor, and other electronic components. The writer really hopes this skripsi can be useful to increase the writer’s knowledge in the field of computer technology, electronics,  and computer system, as well as their applicationstoward computer hardware. As the conclusion: the censor used in this prototype consists of two censors and each of them has different functions. This prototye is made in a miniature of a clothes hanger installed with two censors whose function is to detect weather conditions whether it is bright and dark, as well as wet and dry. The censor work is controlled by the program module made to move a motor. This module is directly connected to Arduino Uno R3 based on the command obtained from the censor. For suggestion, this smart clothes hanger is made in prototype which needs further development for real implementation.